Makna Kebersamaan Sosial dalam Masyarakat bagi Penganut Ugamo Malim dan Kristen Protestan di Cipayung - Maichel Natalando Damanik; Gandi Wibowo; Maria Benedicta Dian Savitri (Voice, 2023)
This research aims to explore and understand the meaning of social togetherness in the community carried out by followers of Ugamo Malim and the Protestants. Social togetherness is defined as the interaction, involvement, and relationship between individuals in a community group. Through a field research method with a descriptive qualitative approach, this research focuses on two different communities, namely Ugamo Malim followers and the Protestants. The methodological steps involved data collection through in-depth interviews as the main instrument. Interviews were conducted with three resource persons from each of the Ugamo Malim and the Protestants parties to gain an in-depth understanding of the concept of social togetherness. The qualitative data collected will be carefully analyzed to identify patterns, values, and beliefs that shape the meaning of social togetherness in the two communities. The results of the study are expected to provide a deep insight into how Ugamo Malim followers and the Protestants interpret and experience social togetherness. The comparison between the two groups is expected to identify similarities and differences in perceptions, practices, and values that underlie social togetherness. The implications of this research are expected to contribute to a cross-cultural understanding of the importance of social togetherness in shaping community solidarity and cohesion.